2014
DOI: 10.1103/physrevb.90.054412
|View full text |Cite
|
Sign up to set email alerts
|

Dzyaloshinskii-Moriya interaction and chiral magnetism in3d5dzigzag chains: Tight-binding model andab initiocalculations

Abstract: We investigate the chiral magnetic order in free-standing planar 3d-5d bi-atomic metallic chains (3d: Fe, Co; 5d: Ir, Pt, Au) using first-principles calculations based on density functional theory. We found that the antisymmetric exchange interaction, commonly known as Dzyaloshinskii-Moriya interaction (DMI), contributes significantly to the energetics of the magnetic structure. For the Fe-Pt and Co-Pt chains, the DMI can compete with the isotropic Heisenberg-type exchange interaction and the magneto-crystalli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 49 publications
5
69
3
Order By: Relevance
“…The experimental data presented here gives a full picture of the DW dynamics and DMI of polycrystalline Pt/Co/Ir(t Ir )/Ta multilayers. The chirality of the DWs proved to be left-handed using asymmetric bubble expansion, which is the usual behaviour reported for DWs in both theoretical 34,35,76 and experimental 7,15,59 studies of Co/Pt interfaces, also for Pt/Co/Ir multilayers 17,30,57 . The experimental v(H InP ) curves for these films that were acquired using asymmetrical bubble expansion ( Fig 5(b-h)) do not have the form expected from the simple creep model 16 that is often used to analyse such data (Fig 5(a)).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The experimental data presented here gives a full picture of the DW dynamics and DMI of polycrystalline Pt/Co/Ir(t Ir )/Ta multilayers. The chirality of the DWs proved to be left-handed using asymmetric bubble expansion, which is the usual behaviour reported for DWs in both theoretical 34,35,76 and experimental 7,15,59 studies of Co/Pt interfaces, also for Pt/Co/Ir multilayers 17,30,57 . The experimental v(H InP ) curves for these films that were acquired using asymmetrical bubble expansion ( Fig 5(b-h)) do not have the form expected from the simple creep model 16 that is often used to analyse such data (Fig 5(a)).…”
Section: Resultssupporting
confidence: 71%
“…But the Ir/FM case is not as straightforward as Pt/FM interface. Initially, ab initio calculations proposed that Ir introduces the opposite chirality to Pt 34,35,62 , which was supported by various experimental reports of additive effects 17,36,59,63,64 . Later on, the sign of DMI for Ir was debated when several experimental studies observed right-handed chirality in multilayers including Ir/Co 29,38,60 .…”
Section: Discussionmentioning
confidence: 82%
“…[14][15][16] Understanding of the origin of the DMI and tailoring the DMI is desirable for fundamental reasons and for potential spintronics device applications. Kashid et al provided a theoretical picture of the influence of 3d and 5d metals on the DMI, 17 and several experimental efforts are exploring various choices of non-magnetic heavy metal layers. For instance, it has been found that different choices of 5d heavy metal layers can significantly influence the sign and strength of the DMI.…”
mentioning
confidence: 99%
“…Moreover, the DMI in trilayers composed of a single layer sandwiched between two elements might also be different than the DMI in a bilayer structure, 28 and the sign of the DMI is very sensitive to the details of hybridization between magnetic layers and heavy metal layers. 17 For these reasons, predicting the chirality that results from inserting 5d spacers in multilayer structures may be complicated by layer thickness dependence of electronic structure and by complicated hybridizations.…”
mentioning
confidence: 99%
“…1). This model is derived in a similar way as our previous model for 3d-5d transition metal chains [28], and it captures the essential physics of the DMI in our Mn 1−x Fe x Ge alloys. Based on the DFT results, in our model we neglect the SOC on the Ge atom, while the effects of non-collinearity and SOC on TMs lead to a finite DMI strength, D = |D|, via contribution to the energy of the type move from above the Fermi energy, become occupied and enter the region of d xy -states of opposite spin with increasing the concentration x − that is responsible for the change of sign and local peak in the DMI strength in the vicinity of x c .…”
mentioning
confidence: 99%